Preserving Through Change: Gamal Music in Contemporary Dayak Jawant Culture - Aryandari, Citra; Adenta, Cristoforus Danendra Caesarea (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
This research investigates how Gamal music in the Dayak Jawant community of West Kalimantan, Indonesia has evolved from scared tradition to contemporary cultural expression, examining how these adaptations reflect the negotiation between cultural preservation and modernization. Traditionally integral to rituals and spiritual life, Gamal music has undergone significant transformations through the adoption of new instruments and styles influenced by global and economic factors, as observed during events like the XI Dayak Gawai Week. Through ethnographic methods, this study examines the balance between heritage preservation and innovation. The research explores contested notions of cultural authenticity, indigenous responses to modernity, and music’s role in preserving cultural identity. While acknowledging traditionalist’ concern, this study argues that these adaptations are essential for Gamal music’s continued relevance and survival. By documenting this music evolution, this research contributing to understanding how traditional art forms can develop sustainable pathways forward, maintaining cultural significance while responding to external pressures. This model potentially applies to other indigenous cultural expressions facing similar challenges in rapidly changing environments. This study ultimately reveals how Gamal music serves as a dynamic vehicle for cultural expression, adapting to contemporary context while preserving core communal values.